Down syndrome passed from mother to child. (2014)
Down syndrome is the leading cause of inherited intellectual disability; it is characterized by mental retardation associated to physical growth delay and certain physical traits or features. It is caused by the presence of a third copy of chromosome 21, being this trisomy the most common chromosomal aneuploidy. Women with Down syndrome are less fertile, and pregnancy in these women is rare, although the information on exact statistics of reproduction in these patients is very limited, and they often have difficulties with miscarriage, premature birth, and difficult labor. We report the case of a preterm newborn with Down syndrome passed from her mother; this pregnancy was a result of sexual assault, which is an event that can and should be prevented in this population.